A New Approach to Sustainability: A Moore's Law for Chemistry. Issue 39 (23rd May 2018) - Poliakoff, Martyn; Licence, Peter; George, Michael W.
Abstract : "… How do we have a major impact on delivering sustainable chemistry? Carbon‐neutral laboratories can drive down the environmental costs of chemistry. We propose that sustainable chemistry requires some overarching goal that can be embraced by everyone in the chemical supply chain as well as by the public …" Read more in the Guest Editorial by Martyn Poliakoff, Peter Licence, and Michael W. George.